2021
DOI: 10.3390/molecules26113262
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Caffeic Acid on Diabetes and Its Complications in the Mouse

Abstract: Diabetic dyslipidemia and hyperglycemia contribute to excessive reactive oxygen species (ROS) production, leading to deleterious complications, such as nephropathy, atherosclerosis and cardiac dysfunction, and target major organs in the body. The aim of this study was to investigate the effect of caffeic acid (CA) on mouse weight and survival, serum level of fasting blood glucose (FBG), serum lipid parameters and atherogenic indices, oxidative damage in blood, liver and kidney tissue, pathophysiological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…CA was found able to reduce the levels of endoplasmic reticulum stress markers in the liver after a HFD obese induction [ 72 ]. Besides CA’s ability to revert dyslipidemia by reducing TG and TC, studies have shown that CA was able to revert hepatic steatosis in the long run [ 49 , 73 , 74 , 75 ]. In a recent in vivo study, a 12 week CA supplementation on HFD obese mice revealed that CA was able to reduce body weight and fat accumulation together with readings of improved lipid profile with an increased HDL [ 56 ].…”
Section: Ca Vs Dyslipidemiamentioning
confidence: 99%
“…CA was found able to reduce the levels of endoplasmic reticulum stress markers in the liver after a HFD obese induction [ 72 ]. Besides CA’s ability to revert dyslipidemia by reducing TG and TC, studies have shown that CA was able to revert hepatic steatosis in the long run [ 49 , 73 , 74 , 75 ]. In a recent in vivo study, a 12 week CA supplementation on HFD obese mice revealed that CA was able to reduce body weight and fat accumulation together with readings of improved lipid profile with an increased HDL [ 56 ].…”
Section: Ca Vs Dyslipidemiamentioning
confidence: 99%
“…Coumarin, known to regulate oxidative stress, hyperglycemia, and dipeptidyl peptidase-IV (DPP-IV) ( Singh et al., 2020 ). Caffeic acid supplementation of diabetic mice indicated a protective effect on the kidney and liver, hypolipidemic and hypoglycemic activities ( Oršolić et al., 2021 ). Rosmarinic acid in hyperglycemia reduces plasma glucose level and increase insulin sensitivity ( Ngo et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The unhemolyzed serum was used for the analysis of total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL-C) and low-density lipoprotein (LDL-C) concentrations. All lipid parameters were analyzed based on enzymatic methods as described by [ 15 , 16 , 17 , 18 ]. The liver, kidney and spleen of each rat were dissected and weighed, and tissues were used to determine oxidative and anti-oxidative status by measured the lipid peroxidation, glutathione levels, and catalase activity (CAT) as well as for antioxidative capacity analysis by methods, such as ferric reducing antioxidant power (FRAP) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) •+ free radical scavenging activity.…”
Section: Methodsmentioning
confidence: 99%
“…The unhemolyzed serum were used for the analysis of TC, TG, HDL-C and LDL-C concentrations. All lipid parameters were analyzed based on the enzymatic methods as described by [ 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation